The Role Of The Indonesian Constitutional Court For Adjudication Of Economic, Social Rights And Effective Culture - Umi Qalsum (JUSTICES: Journal of Law, 2023)
The Indonesian Constitutional Court has played an important role and function to protect and fulfill human rights in the Indonesian legal system including economic, social and cultural rights through judicial review powers. This confirms that social and economic rights are rights that can be legally justified and are part of the constitutional mandate. This means that judicial review decisions require the State to behave in accordance with the legal thresholds decided by the Court. Undoubtedly, compliance with the decision will reveal facts that are indisputable for the fulfillment of state behavior. However, it seems that there are still many considerations, emphasis, and reasons to reduce or ignore the threshold for the application of the Court's decision. The complexity of specific actors, institutions, authorities, levels of implementation, and orientation of policies, programs, measures, and funds reduces the threshold.